Scalable microwave-assisted continuous flow synthesis of CuO nanoparticles and their thermal conductivity applications as nanofluids - Nikam, Arun V.; Dadwal, Arun H. (Advanced Powder Technology, 2019)
We have demonstrated the novel and scalable synthesis of CuO nanoparticles by an integration of microwave and flow synthesis. The shape and size of CuO nanoparticles were tuned by changing the concentration of copper precursor. The production rate of CuO nanoparticles was found to be 5 g/h with 70% conversion of copper acetate into the CuO nanoparticles. The thermal conductivity of CuO nanofluid prepared in ethylene glycol showed linear enhancement with increase in the volume content of CuO nanoparticles produced in batch and flow reactors. (C) 2018 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Flow synthesis; Microwave; Nanofluids; Nanoparticles; scale-up; Thermal conductivity